2010
DOI: 10.1681/asn.2009070784
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–Phenotype Correlation in X-Linked Alport Syndrome

Abstract: Mutations in the COL4A5 gene cause X-linked Alport syndrome (XLAS). Understanding the correlation between clinical manifestations and the underlying mutations adds prognostic value to genetic testing, which is increasingly available. Our aim was to determine the association between genotype and phenotype in 681 affected male participants with XLAS from 175 US families. Hearing loss and ocular changes were present in 67 and 30% of participants, respectively. Average age of participants at onset of ESRD was 37 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
229
8
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(255 citation statements)
references
References 31 publications
13
229
8
5
Order By: Relevance
“…Finally, correlation between the severity of renal involvement and extrarenal symptoms is well established in X-AS (3,4,20,27). Likewise, we also observed that patients with early-onset CKD developed deafness earlier.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Finally, correlation between the severity of renal involvement and extrarenal symptoms is well established in X-AS (3,4,20,27). Likewise, we also observed that patients with early-onset CKD developed deafness earlier.…”
Section: Discussionsupporting
confidence: 79%
“…This is due, at least in part, to differences in the severity of COL4A5 mutations, as indicated by the demonstration of genotype-phenotype correlations (albeit less robust than correlations in other renal diseases) (3,4). More specifically, associations between the type of mutation and the clinical evolution were observed after patients were grouped per category of mutation (3,4,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…2 This milder phenotype is associated with unique genotypes such as missense or in-frame variants in COL4A5. [3][4][5] We previously reported a male XLAS patient with a missense COL4A5 variant who showed only hematuria without proteinuria at the age of 33. 18 We also reported a male patient with a somatic COL4A5 variant who showed hematuria and mild proteinuria at the age of 8 years.…”
Section: Discussionmentioning
confidence: 99%
“…2 These two phenotypes are partially related to the genotype; for example, missense variants or in-frame variants of COL4A5 were reported in cases of later-onset ESRD. [3][4][5] We recently reported that 29% of male XLAS patients expressed the α5(IV) chain in the glomerulus and showed milder clinical manifestations. 6 Interestingly, all α5(IV)-positive patients possessed non-truncating variants (n = 13) or somatic mosaic variants (n = 2) of COL4A5.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically the natural history of the nephropathy and other extrarenal lesions are quite variable. A number of researchers have attempted to link genotypes in Alport syndrome to phenotypes (Bekheirnia et al, 2010, Gross et al, 2002, Jais et al, 2000. Gross and colleagues have proposed a classification linking phenotype and genotype into three categories (Gross et al, 2002).…”
Section: Genotype-phenotype Correlation In X-linked Alport Syndromementioning
confidence: 99%